2016
DOI: 10.1016/j.ophtha.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The Philadelphia Glaucoma Detection and Treatment Project

Abstract: Purpose To evaluate the detection rates of glaucoma-related diagnoses and the initial treatments received in the Philadelphia Glaucoma Detection and Treatment Project, a community-based initiative aimed at improving the detection, treatment, and follow-up care of individuals at risk for glaucoma. Design Retrospective analysis. Participants A total of 1649 individuals at risk for glaucoma who were examined and treated in 43 community centers located in underserved communities of Philadelphia. Methods Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
1
21
0
5
Order By: Relevance
“…Our detection rates were comparable with prior screening programmes that focused on high-risk populations 27. However, a high number of narrow angle cases was detected.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our detection rates were comparable with prior screening programmes that focused on high-risk populations 27. However, a high number of narrow angle cases was detected.…”
Section: Discussionsupporting
confidence: 83%
“…PGDTP programme sites were located in neighbourhoods with high rates of poverty as compared with the national average because the low-income older minority population is at high risk for glaucoma and is typically underserved in eyecare 26. Inclusion was based on meeting one of the following criteria: (1) African–American ≥50 years, (2) ≥60 years of age and of any race or (3) family history of glaucoma 27. The educational workshops aimed to increase awareness about glaucoma and its symptoms, warning signs and risks.…”
Section: Methodsmentioning
confidence: 99%
“…19 In contrast, an American reported that 65% of glaucoma patients had hypertension. 20 Authors are at a loss to explain the lower rate of hypertension noted in our study.…”
Section: Discussionmentioning
confidence: 59%
“…29 However, subsequent studies have suggested that screening in populations at high risk for glaucoma is effective. 30,31 A systematic review of teleglaucoma screening estimated its sensitivity as 83.2% and specificity as 79.0%. 28 Diagnostic consultation.…”
Section: Types Of Teleglaucoma Programsmentioning
confidence: 99%